Optical coherence tomography-angiography for anterior uveal tract evaluation in normal subjects and in pathology - T. N. Kiseleva; S. V. Saakyan; V. V. Makukhina; K. V. Lugovkina; S. V. Milash; N. F. Musova; N. S. Izmailova; A. A. Zharov (Российский офтальмологический журнал)
Purpose: to assess the potentials of optical coherence tomography-angiography (OCTA) in the evaluation of anterior segment (AS) uveal vessels in normal and pathological conditions.Material and methods. 20 healthy volunteers (40 eyes) with no ophthalmic pathology (the control group) and 85 previously untreated patients (85 eyes) with suspected tumors of the irido-ciliary area (the iris, the ciliary body and the peripheral sections of the choroid) were examined. All participants had optical coherence tomography (OCT) and OCTA of AS, with the qualitative assessment of scans (vessels pattern, lumen, tortuosity) and the quantitative assessment (vessel density index, VD%, for the affected zone). In ciliary body or choroid pathologies, VD index was measured for the conjunctiva in the focus projection. VD index included mean and local VD, as well as VD of perifocal tissues. In addition, B-mode ultrasound scanning and ultrasound biomicroscopy were performed.Results. OCTA scans in 4 sectors of the normal iris showed a predominantly radial pattern of conjunctival vessels positioning, with their lumen remaining the same along their entire visible length. The lowest VD value (38.5%) was registered in the temporal iris segment, while the highest (43.9%) was revealed in the inferior quadrant. In the iris tumors area, intrinsic vascularity molded in various vascular patterns was observed. Melanomas could be suspected because of the vessels oriented along the axis of the tumor and by non-uniform lumen of the vessels.Conclusion. AS-OCTA is an informative method for the visualization of iris vessels in normal conditions and in iris pathology and may be considered a valuable addition to the standard visualization techniques.